ECB vs Council vs Commission : monetary and fiscal policy interactions in the EMU when cyclical conditions are uncertain - Balboni, Fabio; Buti, Marco; Larch, Martin; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2007)
This paper examines economic policy interactions in the Economic and Monetary Union when the assessment of cyclical conditions in real time is surrounded by uncertainty. On the basis of a simple stylised model it shows that different views about the output gap on the side of the policy players - the Council of the European Union, the European Commission and the European Central Bank - can affect the equilibrium outcome in terms of output, inflation, the budget deficit and the interest rate. More specifically, if fiscal and monetary policy decisions are taken simultaneously diverging views about the cycle can give rise to excessive activism as policy players try to push economic variables into opposite directions. The costs of such policy conflicts can be reduced by agreeing on a common assessment of the cycle, by constraining policy variables, by increasing the weight of fiscally conservative institutions. Another way to sidestep policy conflicts ensuing from diverging views of the cycle is to take policy decisions sequentially, as is the case in a Stackelberg-type of interaction. To the extent that misperceptions are random, the leader, who moves first, will assume that the follower's assessment will be in line with its own view of the cycle. This effectively precludes the kind of frictions arising in a simultaneous setup, because the leader cannot backtrack. For a given misperception of the cycle, the impact on the policy instruments and on output and inflation are generally smaller in the Stackelberg equilibrium as compared to a Nash outcome.
Economic Papers